Active vibration control of a flexible robot link using piezoelectric actuators - DARREN WILLIAMS (2022)
Nuisance vibrations are a concern throughout the engineering realm, and many re-searchers are dedicated to ﬁnding a solution to attenuate them. This research primarily focusses upon the suppression of vibrations in a robot system, with the control system being designed so that it is both aﬀordable and lightweight. Such constraints aim to provide a solution that may be utilised in a variety of applications. The utilisation of piezoelectric elements as both actuators and sensors provides several advantages in that they are lightweight, easily integrated into an existing system and have a good force to weight ratio when used as actuators. To read and control these elements a single board computer was employed, in acknowledgement of the constraining parameters of the design. The amalgamation of vibration control and robotics has lent to the re-search being conducted with separate objectives set, isolating certain elements of the overall system design for validation. Ultimately, these separate investigations progress to the integration of the robot and control systems prior to further research concerning nonlinear vibrations, dynamic control and the discrete-time domain modelling of the system.This research ﬁrst investigates the viability of the chosen components as a vibration attenuation solution. In addition, analytical models of the system have been created, for two types of sensors to determine the most eﬀective; an inertial measurement unit and a collocated pair of piezoelectric sensors. These models are based on Euler-Bernoulli beam theory and aim to validate the control theory through a comparison of the experimental data. These experiments isolate the vibration problem from a robot system through the investigation of the control of a long slender beam envisioned as a robot manipulator link, but excited using a shaker platform in a sinusoidal manner. An observation of the theory related to the voltage produced by the piezoelectric elements, suggests that even with the application of only proportional control by the system, the controlled output would have components indicative of both proportional and derivative control. This observation and the underlying theory are further analysed within this research.The next objectives are to compare the performance of the control system developed in this research which utilises a Raspberry Pi 3B+ [1] with one that employs a dSPACE MicroLabBox [2], and to determine the suitability of the former for use with robot sys-tems. With the former ensuring that the constraints placed on the design, those which inﬂuenced the selection of the components, does not conclude to the dSPACE Micro-LabBox system being overtly preferable. The latter investigates both the impact of the system’s inclusion on the functionality of the system and the system’s perform-ance with respect to the intended application. The KUKA LBR iiwa 7 R800 [3] robot manipulator is utilised to satisfy this objective, wherein the link is mounted on the end eﬀector of the manipulator acting as an eighth link. The ﬁnal investigation in this research pertains to the attenuation of nonlinear vibrations experienced by a robot manipulator link. Additional components were added to the link to induce a geometric nonlinearity in the system. An analytical model of the amended system was created to validate the theory through comparison with experimental results. The control system was employed for multiple cases to ascertain the level of its performance with regards to the suppression of nonlinear vibrations.